Influence of balloon design, plaque material composition, and balloon sizing on acute post angioplasty outcomes: An implicit finite element analysis. (31st May 2021) - Helou, Bernard; Bel‐Brunon, Aline; Dupont, Claire; Ye, Wenfeng; Silvestro, Claudio; Rochette, Michel; Lucas, Antoine; Kaladji, Adrien; Haigron, Pascal
Abstract: In this work we propose a generic modeling approach for simulating percutaneous transluminal angioplasty (PTA) endovascular treatment, and evaluating the influence of balloon design, plaque composition, and balloon sizing on acute post‐procedural outcomes right after PTA, without stent implantation. Clinically‐used PTA balloons were classified into two categories according to their compliance characteristics, and were modeled correspondingly. Self‐defined elastoplastic constitutive laws were implemented within the plaque and artery models, after calibration based on experimental and clinical data. Finite element method (FEM) implicit solver was used to simulate balloon inflation and deflation. Besides balloon profile at max inflation, results are mainly assessed in terms of the elastic recoil ratio (ERR) and lumen gain ratio (LGR) obtained immediately after PTA. No variations in ERR nor LGR values were detected when the balloon design changed, despite the differences observed in their profile at max inflation. Moreover, LGR and ERR inversely varied with the augmentation of calcification level within the plaque (−11% vs. +4% respectively, from fully lipidic to fully calcified plaque). Furthermore, results showed a direct correlation between balloon sizing and LGR and ERR, with noticeably higher rates of change for LGR (+18% and +2% for LGR and ERR respectively for a calcified plaque and a balloon pressure increasing from 10 to 14 atm). However a larger LGR comes with a higher risk of arterial rupture. This proposed methodology opens the way for evaluation of angioplasty balloon selections towards clinical procedure optimization. Abstract : Despite the difference observed in balloons profiles at max inflation when changing the balloon design, no variations were detected in the obtained elastic recoil ratio (ERR) or lumen gain ratio (LGR) immediately after percutaneous transluminal angioplasty (PTA). Moreover, ERR and LGR inversely varied with calcification level growth within the plaque, with the largest LGR obtained when stenosis had no calcifications. Simulation results illustrate that unlike design, balloon sizing has a significant impact on the attained lumen gain after PTA, but might increase arterial injury risk as well.